2022
DOI: 10.1021/acsomega.1c07088
|View full text |Cite
|
Sign up to set email alerts
|

Use of Ambipolar Dual-Gate Carbon Nanotube Field-Effect Transistor to Configure Exclusive-OR Gate

Abstract: As the physical scaling limit of silicon-based integrated circuits is approached, new materials and device structures become necessary. The exclusive-OR (XOR) gate is a basic logic gate performed as a building block for digital adder and encrypted circuits. Here, we suggest that using the ambipolar property of carbon nanotubes and the threshold modulation ability of dual-gate field-effect transistors, an XOR gate can be constructed in only one transistor. For a traditional XOR gate, 4 to 6 transistors are need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…16−19 Altogether, air-stable NMDCs in the reduced dimension may exhibit better device performance and tunability via defect engineering for future applications in logic circuits. 20 Recently, palladium diselenide (PdSe 2 ), a Group 10 NMDC, has been explored and recognized as a highly air-stable layered material with a unique puckered pentagonal morphology. 13 Usually, puckered configuration exhibits novel anisotropic properties which is rarely found in the family of 2D materials.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16−19 Altogether, air-stable NMDCs in the reduced dimension may exhibit better device performance and tunability via defect engineering for future applications in logic circuits. 20 Recently, palladium diselenide (PdSe 2 ), a Group 10 NMDC, has been explored and recognized as a highly air-stable layered material with a unique puckered pentagonal morphology. 13 Usually, puckered configuration exhibits novel anisotropic properties which is rarely found in the family of 2D materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In contrast to the conventional Group 6 TMDCs, NMDCs with group 10 elements possess largely occupied d -orbitals (more than half-filled) of the noble metals and highly hybridized p z orbitals of the chalcogen atoms which may lead to strong interlayer coupling as well as layer dependent band gap, as observed in one of the compounds from the NMDC family, PtS 2 (∼0.2 eV in bulk and ∼1.6 eV in the monolayer). Additionally, it has been predicted that a coordinatively unsaturated noble metal, like Pd, will have a much higher O 2 adsorption energy barrier (∼1.2 eV) than Group 6 elements which might be the reason for high air-stability at the edges. , Recent experimental study has confirmed that the device performance of PtSe 2 FET remains nearly unchanged after 5 months of air-exposure . Apart from the air-stability and layer dependence, the electronic properties of these materials vary extensively due to surface vacancy defects introduced during the growth and exfoliation process or can be further tuned by doping. Altogether, air-stable NMDCs in the reduced dimension may exhibit better device performance and tunability via defect engineering for future applications in logic circuits …”
Section: Introductionmentioning
confidence: 99%
“…Apart from the air-stability and layer dependence, the electronic properties of these materials vary extensively due to surface vacancy defects introduced during the growth and exfoliation process or can be further tuned by doping [16][17][18][19]. Altogether, air-stable NMDCs in the reduced dimension may exhibit better device performance and tunability via defect engineering for future applications in logic circuits [20].…”
mentioning
confidence: 99%